2010
DOI: 10.1093/ejo/cjq094
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinant factors of malocclusion in children with special needs

Abstract: Careful attention to malocclusion in children with special needs leads to a considerable improvement in the quality of life. The present study analysed the prevalence of malocclusion in children with Down syndrome (DS) and cerebral palsy (CP) as well as associations with individual, socio-economic, and behavioural factors. A cross-sectional study was carried out that included 181 mothers and their children with DS and CP (aged 3-12 years) at two institutions for individuals with special needs in Rio de Janeiro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
43
1
12

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 25 publications
5
43
1
12
Order By: Relevance
“…Meanwhile, deep bite incidence in neuropsychological disabilities may be due to Down's syndrome members of the group who are reported to have reduced vertical dimension of the maxilla and mandible, short teeth, forward rotation of maxillary and mandibular planes [50]. The present study found a low prevalence of posterior crossbite (5.4%) than that obtained by Oliveira et al, [51] (21.5%), among children with neuropsychological disabilities; this may also be contributed to the age differences of the studied populations. Also, different methods of scoring malocclusions may have contributed to this difference.…”
Section: Discussioncontrasting
confidence: 47%
“…Meanwhile, deep bite incidence in neuropsychological disabilities may be due to Down's syndrome members of the group who are reported to have reduced vertical dimension of the maxilla and mandible, short teeth, forward rotation of maxillary and mandibular planes [50]. The present study found a low prevalence of posterior crossbite (5.4%) than that obtained by Oliveira et al, [51] (21.5%), among children with neuropsychological disabilities; this may also be contributed to the age differences of the studied populations. Also, different methods of scoring malocclusions may have contributed to this difference.…”
Section: Discussioncontrasting
confidence: 47%
“…The prevalence of definite and severe malocclusions is usually higher for special needs groups and it also has a noticeable effect that could affect their daily routine, such as facing discrimination due to their appearance, issues with functions, such as mastication, swallowing, and speech. 14,15 Orthodontic services have normally been neglected for this group of children with special needs. This study compared the occurrence of dental occlusal anomalies and found an increased prevalence of class III malocclusion in the DS children compared with the autism subject who had a higher prevalence of class I.…”
Section: Discussionmentioning
confidence: 99%
“…The health care professional should have an integral and multidisciplinary role in motivating parents or guardians to seek oral care at young age. 15 A proper approach by health care professionals and policymakers should aim at reducing the prevalence of malocclusion in these special group children, thereby developing and improving their quality of life. Furthermore, the public or national health care services should draft suitable policies, such as education, motivating the parents that could significantly benefit in preventing or treating malocclusions.…”
Section: Discussionmentioning
confidence: 99%
“…34 Por sua vez, na dentição permanente, a má oclusão muito severa foi encontrada de forma prevalente, à semelhança de outros estudos brasileiros. 29,35 Tais achados podem ser explicados pela frequente presença de disfunções motoras na musculatura orofacial, respiração bucal, movimento ou posicionamento inadequado da língua e reflexos involuntários nas crianças e adolescentes com paralisia cerebral.…”
Section: Discussionunclassified